Evaluating and optimising preoperative physical fitness to enhance postoperative outcome in major surgery - MORAN, JONATHAN JOSEPH (Trinity College Dublin. School of Medicine. Discipline of Physiotherapy, 2018)
Higher levels of physical fitness are associated with numerous health benefits such as improved cardiovascular health, respiratory health, and musculoskeletal health (Heyward, 2010, Warburton et al., 2006). Current guidelines for perioperative risk assessment and modification lack any consensus on the role of preoperative physical fitness. For example, the NICE guidelines provide a number of recommendations for preoperative testing and report cardiopulmonary exercise testing (CPET) requires further research to justify its ability to predict perioperative risk (2016). Furthermore, enhanced recovery after surgery (ERAS) pathways have been developed and implemented in a number of surgical specialities such as colorectal surgery (Khan et al., 2009). These pathways are designed to improve postoperative recovery, however they neglect to address the role of preoperative exercise therapy, which is a recognised component of the preoperative pathway in thoracic surgery (Nagarajan et al., 2011, Benzo et al., 2011). The aim of this thesis is to assess the role of preoperative physical fitness in influencing postoperative recovery. In pursuing this aim, two systematic reviews and two original studies were completed. The first systematic review (Chapter 3) examined the validity of cardiopulmonary exercise testing and field tests of exercise tolerance as a risk assessment method in intra-abdominal surgery. Forty-two full text articles met the inclusion criteria and were included in the qualitative synthesis. The results showed that CPET is an objective measure of cardiorespiratory fitness that is able to identify patients at risk of poor postoperative outcome [morbidity, mortality and prolonged length of stay (LOS)] among various surgical procedures e.g. hepatic resection. Despite this, the areas of colorectal, renal transplant, upper gastrointestinal, and bariatric surgery require further research to draw conclusions concerning the ability of CPET to predict postoperative outcome. In addition, field tests of exercise tolerance offer a less robust method of identifying high-risk patients as due to the small number of studies included (n=6). The aim of the observational study in Chapter 4 was to address the findings of the previous review (Chapter 3) and identify a CPET derived cut-point predictive of postoperative outcome in colorectal surgery. In addition, this study assessed if other components of physical fitness such as muscle strength, could predict postoperative outcome. The results of this study demonstrated agreement with Chapter 3 reporting that lower cardiorespiratory fitness (Ventilatory threshold <11.95 ml/kg/min), measured using CPET, was significantly associated with postoperative complications and hospital LOS following colorectal surgery. The ability of CPET to predict mortality is unclear as there were no reported instances of mortality. Measures of physical fitness including grip strength, inspiratory muscle strength and subjective levels of physical activity did not demonstrate significant relationships with postoperative outcome (p<0.05). Patients with higher levels of preoperative physical fitness had a reduced risk of poor postoperative outcome, therefore the aim of Chapter 5 was to assess if preoperative exercise interventions designed to increase preoperative physical fitness translates to a reduction in postoperative risk. This systematic review identified nine studies and included them in a quantitative meta-analysis. Preoperative exercise interventions consisting of inspiratory muscle training, aerobic exercise, and resistance training decreases the incidence of all-cause postoperative complications in patients undergoing intra-abdominal surgery. This effect was strongest when prehabilitation was compared to usual care (no treatment or breathing exercises). Prehabilitation also significantly improved preoperative physical fitness as measured by inspiratory muscle strength and cardiopulmonary exercise testing. It is unclear if prehabilitation influenced postoperative LOS after intra-abdominal surgery, as the number of studies contributing to the Forest plot was low (n=4). Results should be interpreted with caution, as the quality of included studies measured via the GRADEPro was ?very low?, demonstrating the need for high quality RCT?s to validate the use of preoperative exercise programmes. Furthermore, current exercise prehabilitation protocols are longer (4-6 weeks) than the available duration between decision to treat and surgery as outlined by the National Health Service (31 days). Therefore, clinicians are presented with a difficult decision; proceed directly to surgery and forgo prehabilitation, or delay surgery to allow time for prehabilitation and risk metastatic spread. Chapter 6 aimed to address this shortcoming of the literature by implementing a high intensity interval training programme within the current colorectal and thoracic surgery pathway. Exercise interventions of relatively high intensity have been reported to have low adherence rates (16% completion rates, Carli et al., 2010), therefore the feasibility of a preoperative HIIT programme should first be established to ensure this intervention will have adequate compliance and adherence rates. Subsequently, the PHIIT trial demonstrated high adherence (84%) and compliance rates (88%) in a preoperative HIIT programme, among 16 patients scheduled for colorectal (n=7) and thoracic (n=9) cancer surgery. Furthermore, there were no adverse events related to the disease or exercise intervention. Cardiorespiratory fitness increased significantly as measured by VT (+1.55 ml/kg/min) and VO2peak (+1.57 ml/kg/min) following a mean of 7 (SD: 3) preoperative HIIT sessions, however this was a secondary objective and the study was not sufficiently powered to detect true changes in cardiorespiratory fitness.
APPROVED
Keywords: surgery; physical fitness; preoperative